(\(\frac{3}{\sqrt{x}-1}+\frac{1}{\sqrt{x+1}}:\frac{1}{\sqrt{x}+1}\))
K
Khách
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Những câu hỏi liên quan
22 tháng 6 2016
c) \(C=\frac{\left(2\sqrt{x}+x\right)\left(\sqrt{x}+1\right)-\left(x\sqrt{x}-1\right)}{\left(x\sqrt{x}-1\right)\left(\sqrt{x}+1\right)}:\frac{x+\sqrt{x}+1-\left(\sqrt{x}+2\right)}{x+\sqrt{x}+1}=\)
\(C=\frac{x\sqrt{x}+2x+x+2\sqrt{x}-x\sqrt{x}+1}{\left(\left(\sqrt{x}\right)^3-1\right)\left(\sqrt{x}+1\right)}\times\frac{x+\sqrt{x}+1}{x-1}=\)
\(C=\frac{3x+2\sqrt{x}+1}{\left(\sqrt{x}-1\right)\left(x+\sqrt{x}+1\right)\left(\sqrt{x}+1\right)}\times\frac{x+\sqrt{x}+1}{x-1}=\)
\(C=\frac{3x+2\sqrt{x}+1}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+1\right)}\times\frac{1}{x-1}=\)
\(C=\frac{3x+2\sqrt{x}+1}{x-1}\times\frac{1}{x-1}=\frac{3x+2\sqrt{x}+1}{\left(x-1\right)^2}.\)
\(\left(\frac{3}{\sqrt{x}-1}+\frac{1}{\sqrt{x+1}}:\frac{1}{\sqrt{x}+1}\right)\)
\(=\left(\frac{3}{\sqrt{x}-1}+\frac{\sqrt{x}+1}{\sqrt{x+1}}\right)\)
\(=\frac{3\left(\sqrt{x}+1\right)+x-1}{\left(\sqrt{x}-1\right)\sqrt{x+1}}\)
\(=\frac{\left(\sqrt{x}-1\right)\left(\sqrt{x}+2\right)}{\left(\sqrt{x}-1\right)\sqrt{x+1}}=\frac{\sqrt{x}+2}{\sqrt{x+1}}\)